Proceso administrativo en el Centro Médico Familiar “Cemefa-Salud” en la ciudad de Babahoyo, periodo 2023. - Rodríguez Amat, Bolter Harrison (2024)
The case study entitled: Administrative Process of the Family Medical Center "CEMEFA-SALUD" in the city of Babahoyo, period 2023. Its general objective is to analyse administrative processes; since the existing problem is due to the lack of coordination on the part of the administration, this is manifested in the delay in the attention to users, errors in the management of information when scheduling medical appointments, there is also a lack of planning in the registry of clinical records. This includes the impact on planning, organisation, direction and control, Therefore, the present case study aims to address the problem to ensure the development of organizational strategies and highlight the importance of administrative processes in the operation of the company, to improve the operativity, effectiveness and efficiency. In addition, various research tools such as the SWOT survey and matrix have been established to examine different aspects, with the aim of identifying areas of incidence that need improvement. In this sense, it is recommended that the Family Medical Center "CEMEFA-SALUD" take advantage of the information gathered in the present case study. This will make it possible to understand the stages of the administrative process, guide the development of new strategies, improve internal and external factors, which will contribute to the competitive advantage in the market and improve its operational efficiency, significantly improving the working climate and overall performance of the company.